2021
DOI: 10.1038/s41598-020-80438-3
|View full text |Cite|
|
Sign up to set email alerts
|

Nanodiamond surface chemistry controls assembly of polypyrrole and generation of photovoltage

Abstract: Nanoscale composite of detonation nanodiamond (DND) and polypyrrole (PPy) as a representative of organic light-harvesting polymers is explored for energy generation, using nanodiamond as an inorganic electron acceptor. We present a technology for the composite layer-by-layer synthesis that is suitable for solar cell fabrication. The formation, pronounced material interaction, and photovoltaic properties of DND-PPy composites are characterized down to nanoscale by atomic force microscopy, infrared spectroscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…In the FTIR spectra (Figure c), the typical peaks at 3435, 1635, and 1350 cm –1 correspond to the terminal oxygen-containing groups (i.e., −OH and Ti–O) of Ti 2 C 3 T x MXene . In addition to the characteristic peaks of MXene, the absorption peaks of PPy at 3210, 1122, 1074, and 892 cm –1 corresponding to the N–H deformation vibration, ring deformation, and stretching vibration of polaron (C–N + ) and the bipolaron (CN + ) are also observed on the FTIR spectrum of the MXene@PPy hybrid, ,, which indicates the existence of PPy chains on MXene nanosheets. Besides, the slightly stronger absorption in the UV–vis spectrum of the MXene@PPy hybrid over 1000 nm compared to MXene confirms the NIR light absorption of PPy (Figure S2).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the FTIR spectra (Figure c), the typical peaks at 3435, 1635, and 1350 cm –1 correspond to the terminal oxygen-containing groups (i.e., −OH and Ti–O) of Ti 2 C 3 T x MXene . In addition to the characteristic peaks of MXene, the absorption peaks of PPy at 3210, 1122, 1074, and 892 cm –1 corresponding to the N–H deformation vibration, ring deformation, and stretching vibration of polaron (C–N + ) and the bipolaron (CN + ) are also observed on the FTIR spectrum of the MXene@PPy hybrid, ,, which indicates the existence of PPy chains on MXene nanosheets. Besides, the slightly stronger absorption in the UV–vis spectrum of the MXene@PPy hybrid over 1000 nm compared to MXene confirms the NIR light absorption of PPy (Figure S2).…”
Section: Results and Discussionmentioning
confidence: 99%
“…To solve these problems, Fan et al demonstrated a solution of surface modifying a silver nanoparticle (AgNP) onto MXene, which not only combined the plasmonic effect of nanometals leading to the enhancement of photothermal response but also consumed part of rich active groups with the improvement in oxidation resistance . By contrast, the low-cost polypyrrole (PPy), as a typical conductive polymer, shows an excellent light absorption in the near-infrared (NIR) region due to the conjugation effect. Moreover, the easy synthesis process makes PPy more suitable to modify MXene. However, the synergetic photothermal effects of PPy and MXene used as photothermal conversion materials, especially in the field of transparent photothermal conversion applications, have not yet been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, in bulk semiconducting nanoparticles, the spatial charge separation in different crystal facets has been well recognized as a potential strategy to improve the efficiency of charge carrier separation. , For example, DFT studies on the van der Waals-bonded BiOBr/BiOI bilayer spatially separate the photogenerated electrons and holes to facilitate the water-splitting reaction . Similarly, in a composite of nanodiamond-polypyrrole, the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) are spatially separated to significantly enhance photovoltaic properties . Thus, the photo-excitation can create spatially separated charge carriers in g-C 3 N 4 nanoribbons.…”
Section: Resultsmentioning
confidence: 99%
“…41 Similarly, in a composite of nanodiamondpolypyrrole, the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) are spatially separated to significantly enhance photovoltaic properties. 42 Thus, the photo-excitation can create spatially separated charge carriers in g-C 3 N 4 nanoribbons.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The surface charges of different ratios of Ly/CRG composite systems (1:7, 1:5, 1:3, 1:2, 1:1, 2:1, 3:1) were determined using a ζ-potentiometer. The electrophoretic mobility of the relationship between UE and zeta potential satisfies the Henry equation (Miliaieva et al, 2021) (Equation 1):…”
Section: ζ Potential Of Ly/crg Complexmentioning
confidence: 99%